Efficacy of periodontal soft tissue augmentation prior to orthodontic treatment on preventing gingival recession: study protocol for a randomised controlled trial. Issue 12 (13th December 2022) - Chen, Jing; Lv, Jiashu; Zhang, Fan; Zhang, Wei; Wang, Yuhui; Xu, Yichen; Pan, Yichen; Li, Qiang
Abstract : Introduction: In adult patients with thin phenotype, gingival recession is obvious in the mandibular incisors after a large amount of lingual tooth movement. A systematic review indicated that soft tissue augmentation before orthodontic treatment might yield satisfactory results with respect to the progression of gingival recession. However, the studies included had a low-to-moderate level of evidence. This study was designed to investigate the efficacy of soft tissue augmentation prior to orthodontic treatment on the prevention of gingival recession. Method and analysis: This is a single-centre, single-blind, randomised controlled, double-armed parallel group comparison trial. This study was initiated in December 2021 and end in December 2025 (anticipated). Patients with mild crowding in the lower arch and a thin gingival type was enrolled and randomly assigned in a 1:1 ratio to either group A (having soft tissue augmentation prior to orthodontic treatment) or group B (having orthodontic treatment only). The planned number of enrolled patients was 48 (24 patients × 2 groups). The primary endpoint was the mean change in recession of the gingival margin. Secondary endpoints included the probing depth, gingival phenotype, frequency of complete root coverage, gingival thickness, width of the keratinised gingiva, clinical attachment level, gingival recession class, full-mouth plaque score, alveolar bone thickness in the faciolingual dimension of the lower anterior teeth and lower incisor inclination. Ethics and dissemination: The study protocol was approved by the Ethical Committee of the Shanghai Stomatological Hospital (certificate number (2021)016). The study was conducted in accordance with the Declaration of Helsinki, the Clinical Trials Act and other current legal regulations in China. Written informed consent was obtained from all the participants. The results of this study will be reported in journal publications. Trial registration number: ChiCTR2100050892.